A Bibliometric Review of E-Mentoring for Professional Development: a Scopus Database Study - Salsabila, Shufi; Kustandi, Cecep; Nurjannah (Journal of Science and Education (JSE), 2024)
This research provides a bibliometric review of e-mentoring for professional development, using the Scopus database to analyze publication trends from 2005 to 2024. The aim of this study was to identify key trends, influential authors, and emerging themes in this field. A total of 335 documents were analyzed using advanced bibliometric methods, including author collaboration analysis, descriptive analysis, keyword occurrence analysis, and citation analysis. The main results showed a significant increase in the number of publications after 2012, highlighting the increasingly recognized important role of e-mentoring in professional development. The analysis also found important peaks in research activity related to global events and technological developments. This study emphasizes the importance of cross disciplinary collaboration and further research into the effectiveness and scalability of e-mentoring. The findings provide valuable insights for educators, policymakers and researchers, and contribute to the development of educational strategies that integrate digital mentoring environments